Theoretical evaluation of heavy metals migration and sorption in soil - Danila, Vaidotas; Vasarevičius, Saulius (International Conference “Environmental Engineering”, 2017)
Heavy metals are one of the group of toxic pollutants in the soil. Over the past years, many researches have been conducted on the migration of heavy metals in soils and various models were developed in order to study the mobility of toxic heavy metals. The convection-dispersion equation is the most commonly used equation for describing the migration of toxic pollutants in the soil. Various properties of the soil influence the mobility of heavy metals: soil pH, texture, sorption character istics. Heavy metals not only migrate in the soil, but also interact with mineral and organic soil particles. The mobility of heavy metals in soils is determined by their partitioning between solid and aqueous phases of the soil. The partitioning of heavy metals between these two phases are described by sorption/desorption, precipitation/dissolution, and redox processes. Natural mineral and organic sorbents present in soils have a strong influence on heavy metals sorption. As these sorbents are usually negatively charged, they attract heavy metals cations through electrostatic force.
Keywords: convection; diffusion; sorption; precipitation; two-site sorption model